Discovering Perspectives on Health and Well-Being from Parents and Teachers of Preschool-Aged Children - Divya Sood; Delawnia Comer-Hagans; Dirk Anderson; Diana Basmajian; Ashley Bohlen; Michelle Grome; Irada Imanova; Kimberly Martin (Scholarworks @ WMU, 2018)
Background: This study explores the concept of health and well-being as perceived by teachers and parents of preschool-aged children in the specific context of a child day care facility. The study also identifies the barriers parents and teachers encounter and the supports they require in promoting the health and well-being of preschool-aged children. Method: A qualitative phenomenological research design combined with a projective technique of Photovoice was used for data collection. A total of eight participants, four teachers and four parents of preschool-aged children from a child day care facility, participated in the study. Results: Several themes were identified related to barriers that parents and teachers face and the supports they require in promoting the health and well-being of preschool-aged children. Conclusions: This study discusses a potential role for occupational therapy practitioners in collaborating with administrators and teachers and parents of preschool-aged children to develop a program to promote the health and well-being of preschool-aged children.